Aplikasi Sistem Keuangan Perbankan Syariah - Fauzi Arif Lubis (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2018)
Islamic banks are based on the principles of partnership, justice, transparency and universality and conduct banking business activities based on sharia principles. Sharia bank activities are an implementation of Islamic economic principles. Islamic banks also operate on the basis of the concept of profit sharing, and do not use interest as a tool to earn income or charge interest on the use of funds and loans. The research aims to find out the meaning of the application of Islamic banking systems. The approach in this study uses a descriptive approach by reducing data, presenting and concluding data. The results of this study are Islamic banks must remain guided by the values of sharia in carrying out its business, the principle of which is guided by the Qur'an and Hadith, the principles applied to Islamic financial institutions include the prohibition on applying interest and forbid usury.